KINERJA PEGAWAI PADA BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL (BPPT-PM) KABUPATEN DONGGALA - Sukmawati, Sukmawati (Katalogis, 2018)
This researth conduted at the office of integrated licensing services agency and investment of donggala regency in order to determine how the employee’s performance in carrying out the task. To measure the performance of employees in this research theory Minner was used. (1988:72), that to see the performance is largely determined by the quality of work, quantity of work, on time, and cooperation. The research carried out by the consideration that it is necessary to know and manage, learn about better employee performance. The research method covered observation, interviews and documentation. The result shows that the performance of employee in the integrated  licensing services agency and investment of Donggala Regency seen from the indicators of research that in the implementation of the quantity of work seen from the punctuality in completing a task  has meet in accordance  with the provisions of the indicators but seen from indicatorsquality of quality  of works execution process tasks employees still get difficulties, especially in the works being done related to the field of technology, organic employees competence or civil servants have not been adequate, about the punctuality indicators, there are still employees who lack discipline seen from in time working hours, as well as the lack of cooperation, especially communication between among employees and employees and the leader it needs to provide training, confidence and more motivation to every employee to increase their competences particularly on technology and increase their discipline and also need to bee balanced with sustainable evaluation for the sake of finding out the successful level and increase the target, goal as the vision and mission of the integrated lincensing services agency and investment of Donggala Regency that have been agreed.